Recent Advances: Molecular Mechanism of RNA Oxidation and Its Role in Various Diseases - Li, Zhe; Chen, Xiatian; Liu, Ziqian; Ye, Wei; Li, Ling; Qian, Lili; Ding, Hongyan; Li, Peifeng; Aung, Lynn Htet Htet (Frontiers in Molecular Biosciences, 2020)
Compared with the research on DNA damage, there are fewer studies on RNA damage, and the damage mechanism remains mostly unknown. Recent studies have shown that RNA is more vulnerable to damage than DNA when the cells are exposed to endogenous and exogenous insults. RNA injury may participate in a variety of disease occurrence and development. RNA not only has important catalytic functions and other housekeeping functions, it also plays a decisive role in the translation of genetic information and protein biosynthesis. Various kinds of stressors, such as ultraviolet, reactive oxygen species, and nitrogen, can cause damage to RNA. It may involve in the development and progression of diseases. In this review, we focused on the relationship between the RNA damage and disease as well as the research progress on the mechanism of RNA damage, which is of great significance for the pathogenesis, diagnosis, and treatment of related diseases.